Epidemiological association of cannabinoid- and drug- exposures and sociodemographic factors with limb reduction defects across USA 1989–2016: A geotemporospatial study. (June 2022) - Reece, Albert Stuart; Hulse, Gary Kenneth
Highlights: Limb reduction rates (LRR) were associated with cannabis use, and THC potency. A sharp increase in LRR rates occurred from the fourth to the fifth quintile. These relationships were robust to adjustment for ethic and economic covariates. They were maintained at geospatiotemporal regression. Cannabis legalization was associated with higher LRR's. Abstract: Background: Reports of major limb defects after prenatal cannabis exposure (PCE) in animals and of human populations in Hawaii, Europe and Australia raise the question of whether the increasing use of cannabis in USA might be spatiotemporally associated with limb reduction rates (LRR) across USA. Methods: Congenital anomaly data was from the National Birth Defects Prevention Network, drug use data was taken from the National Survey of Drug Use and Health (NSDUH), cannabinoid concentration was estimated from Federal seizure data and ethnicity and income data were from the US Census bureau. Geotemporospatial analysis was conducted in R. Results: 436 LRR datapoints were obtained. LRR was significantly associated with cannabis use and tetrahydrocannabinol (THC) exposure and demonstrated prominent cannabis-use quintile effects. A sharp increase in LRR occurred from the fourth to fifth quintiles of cannabis exposure (mean ± S.E.M 3.78 ± 0.38 to 6.66 ± 0.56/10, 000 live births, P = 5.22 × 10 −9 ). In final lagged geospatial models adjusted for ethnicity and income interactive terms including cannabinoids were highly significant and robust to adjustment. States in which cannabis was not legalized had a lower LRR (4.28 v 5.01/10, 000 live births, relative risk reduction = −0.15, (95%C.I. −0.25, −0.02), P = 0.021). Internationally 37–63% of cases are estimated to not be born alive. Their inclusion in these analyzes uniformly intensified the identified effects and the significance of the effect of the cannabis legalization paradigm rose from P = 0.0256 to P = 0.0146 to P = 0.0048 with silent factors of 0%, 36% and 63%, respectively. Conclusion: Therefore a spatiotemporal and dose-dependent association between several cannabinoids including THC and cannabigerol and LRR is reported, is robust to adjustment, is consistent with pathophysiological and preclinical studies, accords with findings elsewhere, is markedly exacerbated in higher exposure quintiles, is exacerbated by cannabis legalization and evidences dose-related intergenerational sequaelae. Graphical abstract: Image, graphical abstract